SOCIO ECONOMIC EFFECTS OF NARCOTIC TRAFFICKING - Dhir, Narinder Singh; Jeet, Shobhna (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Socio-economic problems linked to narcotic trafficking become most severe in areas where drug abuse rates are high. This study examines the impact narcotic trafficking imposes on economic growth and criminal activity and local social organizations in specific countries. The establishment of illegal drug markets deforms lawful business operations, generates increased corruption, decays institutional structures. These factors ultimately reduce both economic output and governmental operational effectiveness. The increasing crime rates with their components such as organized crime and money laundering along with violent offenses create difficulties for law enforcement agencies which overloads the judicial system while producing social instability. Thorough research into Punjab and Haryana shows how extensively narcotic trafficking affects these states in both economic and social aspects. The agricultural areas of Punjab and Haryana have become subject to unauthorized drug traffic which reduces worker performance and creates financial problems through drug dependency. The distribution chain of pharmaceutical opioids through chemists creates a problem because regulatory failures occur when drugs divert to illegal consumers. Narcotic crime proliferation through smuggling networks with drug-related violence has created a critical socio-legal situation that affects young populations and public health standards. This paper elaborates on narcotic trafficking’s effects on political systems plus police departments and drug recovery programs while stressing that addressing drug misuse requires various approaches to defeat economic drug consequences. Solving these problems needs governments to establish strict rules and work together internationally and run awareness programs with community-based rehabilitation initiatives. Implementation of robust policies with socio-economic reform measures represents the necessary approach to limit long-term drug trafficking impacts in Punjab and Haryana and similar affected areas.